Loin des yeux et loin du coeur: Deux hôpitaux militaires canadiens-français au service de la France, 1915--1919 - Litalien, Michel (University of Ottawa (Canada), 2003)
During the First World War, the infantry was the only service in which French Canadians could serve while speaking their mother tongue. But, other than the 22nd Infantry Battalion, there were two more French-Canadian units that saw active service throughout the Great War. These units were the "Hopital general canadien no. 6" (Number 6 Canadian General Hospital), raised by the Medical Faculty of Laval University in Montreal, and the "Hopital stationnaire no. 4" (Number 4 Stationary Hospital) (later augmented and re-named "Hopital general no. 8") [Number 8 General Hospital], whose existence was made possible thanks to the personal fortune of a wealthy Montreal physician, Doctor Arthur Mignault. Although the memory of these two hospitals is still very much alive in France, it is non-existent in Canada. And yet, when these two hospitals were raised in 1915, Montreal's French daily newspapers were very interested in them. Media interest diminished as time passed, and by the spring of 1919 the newspapers barely noted their homecoming. Attempts to publish a history of the accomplishments of these two units were fruitless, the memory of their existence was lost, and they disappeared from our collective consciousness. (Abstract shortened by UMI.)
Keywords: History, Canadian.